The impact of Syrian asylum on Jordanian society (2011-2017) - Alharbi, Mohamad Mannsour
The 'Arab Spring' has been shaped by successive episodes of the revolutions of freedom. It is considered the largest geopolitical movement that has rocked the Arab world and the Middle East since the 1960s, which witnessed the eruption of the socalled national revolution that sanctified the Arab exodus from the yoke of old colonialism and their aspiration to independence, freedom, dignity and national sovereignty, like other nations. Historical experiences with protracted refugee situations show that they are not resolved quickly; on average, they now last close to 20 years before refugees can return home or other solutions are found. The presence of the Syrians in neighbouring countries is likely to be a medium to long-term situation, requiring plans in recognition of this time frame, as well as recognition of the long-term global responsibility to support the refugees and the host countries financially. This study aimed at determining the role played by the Jordanian society during the Syrian crisis in all fields, and to identify the impact of the Syrian crisis on Jordanian society (economy, education, water and agriculture, and health).In order to achieve the objective of the study, a questionnaire was designed as the main tool for collecting data. It included (54) items divided into four variables (economy, education, water and agriculture, and health). The sample comprised of (177) individual's that selected randomly from all employees of the Jordanian Refugee Affairs Directorate of the Ministry ofInterior. After the distribution of the questionnaire and data collection, the SPSS software was used to answer the study questions through the use of descriptive analysis.The study found that there is a great impact of Syrian asylum on Jordanian society in all aspects. The threats facing Jordan, due to Syrian asylum, are not only linked to direct security and mi litary threats; they are, indeed, due to a large number of Jordanians joining the Islamic State Organization and other extremist terrorist organizations in the northern regions. Syrian refugees have exhausted economic infrastructure and resources in Jordan, and Jordan faces significant challenges to its economic resources under Syrian asylum.In the light of the results the study recommended that the Syrian crisis, its continuation and its impact on Jordan require a new course through the holistic approach to transform the Syrian refugee crisis into a development opportunity that positively reflected on host communities and refugees. The current study also suggests further investigation in the development of a model for an alternative economy, education, water and agriculture, and health factor for both refugees and the country host.